2009
DOI: 10.5424/fs/2009182-01055
|View full text |Cite
|
Sign up to set email alerts
|

Radial variation of anatomical features, wood density and decay resistance in teak (Tectona grandis) from two qualities of growing sites and two climatic regions of Costa Rica

Abstract: The objective of this study was to show the radial variation of some anatomic characteristics, wood density and natural durability of teak (Tectona grandis L.F.) growing in Costa Rica. Samples of trees 13 years old were obtained from two growing sites (high and low growing) of plantations established in a humid tropical climate (CHT) and dry tropical climate (CST). The variables measured of the fibers as well as for the rays were not affected by the climate or the type of growing site, except for the length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
0
3
0
15
Order By: Relevance
“…On the other hand, Rudman and Da Costa (1959) established, based on extracted samples, which decay resistance is due to a gradual change either in cell composition or structure as the tree ages (Moya et al, 2009). …”
Section: Relation Between Colour and Decay Resistancementioning
confidence: 99%
“…On the other hand, Rudman and Da Costa (1959) established, based on extracted samples, which decay resistance is due to a gradual change either in cell composition or structure as the tree ages (Moya et al, 2009). …”
Section: Relation Between Colour and Decay Resistancementioning
confidence: 99%
“…La correlación positiva entre el pH y el calcio de las hojas evidencia que a mayor salinidad, más alta será su concentración en el área de la hoja; Bertsch (1995) cita que el pH afecta algunas características de los nutrimentos (calcio, magnesio, potasio y fósforo y nutri mentos menores) en el suelo como: solubilización, disponibilidad y adsorción, lo que se refleja en su nexo con el crecimiento del árbol. Según los resultados de Ypushima (2010), únicamente, el fósforo y el potasio confirmaron correlación The anatomical structure of wood is partly a consequence of environmental factors, as Bhat and Priya (2004) have pointed out for crops aged 21 and 65 years, and Moya et al (2009) for estadística con la altura y el diámetro a la base del tallo. Los niveles establecidos como mínimos para el potasio fueron suficientes para T. grandis en Nayarit.…”
Section: Resultados Y Discusiónunclassified
“…the conditions were adequate for the attack. Moya et al (2009) evaluated the resistance of individuals aged 13 years against P. chrysosporium and G. trabeum, and they also detected no differences between the diverse areas. However, according to the findings of Bhat et al (2005) and Thulasidas and Bhat (2007), trees from humid areas were less resistant to the attacks, and G. trabeum caused a larger weight loss in wood samples aged 35 years; conversely, weight losses with P. chrysosporium were below 10 %, which coincides with the findings of Miller et al (2003) for tropical hard woods of different species in Bolivia.…”
Section: Veracruzmentioning
confidence: 98%
See 1 more Smart Citation
“…In teak wood, Bhat and Priya (2004) established that timber from low fertility sites produces timber with low mechanical resistance, attributed to a higher amount of parenchyma and low fibers content. Studies conducted by Moya and Pérez (2008), Moya et al (2009), Moya and Calvo-Alvarado (2012) and Kokutse et al (2010a, b) showed variations in wood properties due to changes in climatic conditions and soil fertility where trees were planted. Other studies have shown variations in wood properties due to site effect (Bhat et al 2001Kokutse et al 2004;Pérez and Kanninen 2003;Thulasidas and Bhat 2007).…”
Section: Introductionmentioning
confidence: 95%